(untitled) (American Journal of Islam and Society, 2023)
North American Muslims seeking to resolve their private disputes confront multifaceted access to justice issues. Since Islamic marriage and divorce laws do not always align with North American family legislative schemes, Muslims are burdened with trying to simultaneously meet their obligations toward both legal systems. Unlike secular law, Islamic divorce proceedings require either the husband’s eventual consent or the availability of a Muslim judge. They also prescribe substantive obligations and rights for divorcees that are comparable to corollary relief provided by family law statutes. The absence of religious quasi-judicial dispute resolutions poses barriers to Muslims obtaining a religious divorce or annulment, and to acquiring subsequent relief, such as financial settlements and custody, in accordance with their religious beliefs. To respond to these overlapping barriers, this paper analyzes forms of Islamic legal authority to grant religious divorce or annulment, and to mediate or arbitrate corollary relief using religious law. The paper concludes with recommendations for a holistic framework to settle family disputes in compliance with Islamic law and in a legally enforceable manner.